Halothermophilic Cas9 and dCas9 Interaction with Variety sgRNA In-silico - Kenny Lischer; Kholisoh Hayati; Muhammad Haykal Fabian; Fina Amreta Laksmi; Yudhi Nugraha; Hamdan Dwi Rizqi; Riri Fauziyya; Sarmoko; Mohd Shukuri Mohamad Ali (International Journal of Technology)
Industrial bioprocesses often require microorganisms that can adapt to specific conditions, such as halothermophilic bacteria capable of producing biosurfactants with various applications. Enhancing production yield is important, and one approach genetic modification. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) is a highly effective method for genetic editing; however, its use in halothermophilic bacteria remains limited. So far, optimal genetic editing with Cas9 has only been achieved in thermophilic bacteria unsuitable for high-salt environments. For determining optimal CRISPR involves analyzing the binding interaction between sgRNA (single guide RNA) and Cas9 using Molecular Docking in halothermophilic bacteria. This includes preparing the structures of Cas9 and sgRNA, simulating them with HDOCK software, and data analysis. Molecular Docking has advantages such as cost-effectiveness and time efficiency in designing the optimal sgRNA length. Optimization of sgRNA is achieved by varying the lengths of repeat, spacer, and tracrRNA, aiming for the lowest binding energy values and visually feasible designs. For Cas9 from the selected bacterium, Klebsiella pneumoniae, the optimal sgRNA design for Cas9 involves a spacer of 10 nt. In contrast, dCas9 involves a spacer of 10 nt, a repeat of 36 nt, and tracrRNA of 63 nt. The native temperature of the bacteria did not significantly affect the optimal sgRNA length.